(untitled) (Research, Society and Development, 2020)
The aim of this study is to analyze the prevalence of syphilis in pregnancy in the city of Teresina-PI from 2015 to 2019. An integrative literature review study was conducted using searches on the VHL, PUBMED and Google Scholar data platform, to build the article and the epidemiological profile of pregnant women was characterized in terms of age, education, case of congenital syphilis according to the prenatal care performed, treatment of the partner performed, gestational age and treatment schedule prescribed according to data obtained on the DATASUS platform. The results of the present study showed an increasing number of cases over the years, and the number of women with prenatal care performed was high, however, the study points out very high rates of pregnant women with diagnoses of syphilis from the third trimester pregnancy, which indicates a late start of prenatal care. The largest number of cases of syphilis occurred in women with low education and aged between 20 and 29 years due to the great lack of information. In view of this, it is clear that more preventive actions against syphilis are needed for this part of the population that has difficulty accessing information.